PENDIDIKAN MENURUT AL-GHAZALI - Syamsul Kurniawan (AT-TURATS, 2008)
Education reform efforts typically begin with a conceptual perspective before implementation. Thus, developing Islamic education usually begins with a study of a figure and his educational thought. And one of the most influential figures whose thought which has Sufi religious pattern has dominated educational thinking atmosphere over the centuries since his death. The purpose of education according to al-Ghazali was to get closer to Allah. He came with a view that the most noble job is to educate: to become a teacher. Al-Ghazali advised that his students, in the learning process, aim to become scientists who could disseminate their knowledge for the sake of humanity values. Keywords: Al-Ghazali, Thought, Islamic Education.